LPS-Induced Systemic Neonatal Inflammation: Blockage of P2X7R by BBG Decreases Mortality on Rat Pups and Oxidative Stress in Hippocampus of Adult Rats - Silva, Clivandir Severino da; Calió, Michele Longoni; Mosini, Amanda Cristina; Pires, Jaime Moreira; Rêgo, Débora da Silva Bandeira; Mello, Luiz E.; Leslie, Ana Teresa Figueiredo Stochero (Frontiers in Behavioral Neuroscience, 2019)
Neonatal lipopolysaccharide (LPS) exposure-induced brain inflammation has been associated to neuronal injury and facilitates the development of models of neurological disorders in adult rats. The P2X7 receptor (P2X7R) plays a fundamental role in the onset and maintenance of the inflammatory cascade. Brilliant blue G (BBG), a P2X7R antagonist, has been shown to effectively promote neuroinflammatory protection. Here, we have investigated the long-term effects of the neonatal systemic inflammation on hippocampal oxidative stress, anxiety behavior and pain sensitivity in adulthood. We hypothesized that P2X7R blockade is able to modulate the effects of inflammation on these variables. Male and female rat pups received LPS and/or BBG solution intraperitoneally on the first, third, fifth and seventh postnatal days. The survival rate and body weight were evaluated during the experimental procedures. The animals were submitted to behavioral tests for anxiety (elevated plus maze) and nociception (hot-plate and tail flick) and the oxidative stress was measured by superoxide production in the dentate gyrus of the hippocampus using dihydroethidium (DHE) probe. BBG increased the survival rate in lipopolysaccharide treated rats. No significant differences were found regarding anxiety behavior and pain sensitivity between the experimental groups. Systemic neonatal inflammation lead to a higher production of superoxide anion in the dentate gyrus of the hippocampus in adulthood and BBG inhibited that effect. Our data suggest that blocking the activation of the P2X7R during neonatal systemic inflammation may have a potential neuroprotective effect in adulthood.